Electrifying Oxide Model Catalysis: Complex Electrodes Based on Atomically-Defined Oxide Films - Brummel, Olaf; Libuda, Jörg (Catalysis Letters, 2020)
Abstract: By studying complex model catalysts based on well-defined oxide surfaces, fundamental insights have been obtained into the surface chemistry of many heterogeneously catalyzed processes. In this perspective, we summarize a series of studies, in which we have transferred this model catalysis approach to the field of electrocatalysis. Our model electrocatalysts consisted of Pt nanoparticles (NPs) grown on atomically-defined oxide films. Specifically, we used well-ordered Co3O4(111) thin films on an Ir(100) support. The Pt NPs were prepared by physical vapor deposition (PVD) and the particle size was varied from a few nanometers to the sub-nanometer size range. We prepared all model catalysts under ultra-high vacuum (UHV) conditions using a dedicated preparation system. This setup enables us to transfer the model catalysts from UHV into the electrochemical environment to apply various in-situ techniques without exposure to air. We investigated the stability window of pristine Co3O4(111) and Pt/Co3O4(111) using online inductively coupled plasma mass spectrometry (ICPMS), electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), scanning tunneling microscopy (STM), ex-situ emersion X-ray photoelectron spectroscopy (XPS), and low energy electron diffraction (LEED). Within the stability window (pH 10, 0.3–1.1 VRHE) the surface structure of the model electrocatalysts is preserved. We analyzed identical samples both in UHV and in the electrochemical environment. Specifically, we applied synchrotron radiation photoelectron spectroscopy (SR-PES) and ex-situ emersion XPS to analyze the electronic structure and we used infrared reflection absorption spectroscopy (IRAS), temperature programmed desorption (TPD), EC-IRRAS, and cyclic voltammetry (CV) to study CO adsorption and oxidation. The model electrocatalysts show pronounced particle size effects and metal support interactions are shown to play a key role in their catalytic reactivity. Of particular importance is an interfacial Pt oxide, which is stabilized by the oxide support and exists at electrode potentials as low as 0.5 VRHE. Moreover, spillover effects enable new reaction mechanisms, which involve oxygen from the oxide support. This review demonstrates the potential of the model electrocatalysis approach to provide fundamental insights into complex oxide-based electrocatalysis. Graphic Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-01-21
Keywords: CO oxidation; Electrocatalysis; Metal-support interaction; Nanoparticles; Oxide supports; Spillover